Modification of Electrode in Dermatosensory Evoked Potential - Sumai Hamad Jaafer1 , Mohammed Umara Obed2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Somatosensory evoked potential (SSEP) usually done using bipolar surface stimulator of peripheral nerve and recorded by cortical surface or subdermal needle electrodes, in this study we modify an adhesive large surface area, surface stimulator using the same montage and method then compare the result between them. We took nineteen patients of median nerve SSEP, locate and identify the shape of dermatom assigned according to text using large square adhesive surface electrode. The same as the shape of dermatom, this is the cathode electrode, for the anode, a strip has the same length of the cathode with a width of two centimetres placed beneath the cathode, the circular ground band between stimulated and recording electrode. The subjects In this study prepared for routine SSEP study the result obtained of both study compared using statistical method and we found there was a significant different between two method and the modified as higher amplitude using lesser stimulated threshold but not significant different between latency. That’s happened because we increased the surface area of stimulation which means more the motor nerve was stimulated.